Simulation of the spatial distribution of scattered light under illumination of a resonant diffraction grating with structured light - S.N. Khonina; Yu.V. Kapitonov (Компьютерная оптика)
In this paper, a comparative theoretical analysis and numerical simulation of the operation of various types of diffraction gratings in the far field is carried out using a Fourier transform. In more detail is discussed the spatial spectrum of binary amplitude gratings, including the diffraction patterns in the far field and in the focal plane and while taking into account variations in the fill-factor. When analyzing characteristics of experimentally created halide perovskite resonant gratings, the influence of the illuminating beam type on the formation of the first three diffraction orders is considered.